2015
DOI: 10.1038/ismej.2015.134
|View full text |Cite
|
Sign up to set email alerts
|

A natural odor attraction between lactic acid bacteria and the nematode Caenorhabditis elegans

Abstract: Animal predators can track prey using their keen sense of smell. The bacteriovorous nematode Caenorhabditis elegans employs sensitive olfactory sensory neurons that express vertebrate-like odor receptors to locate bacteria. C. elegans displays odor-related behaviors such as attraction, aversion and adaptation, but the ecological significance of these behaviors is not known. Using a combination of food microbiology and genetics, we elucidate a possible predator-prey relationship between C. elegans and lactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…Although NO molecules have high permeability through the membranes of lactobacillus and intracellular structures due to their small sizes. This result indicates that bacterial NO is generally beneficial to worms [70] indicates NO Promotes heat – tolerance (stress tolerance) in C. elegans [7173]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NO molecules have high permeability through the membranes of lactobacillus and intracellular structures due to their small sizes. This result indicates that bacterial NO is generally beneficial to worms [70] indicates NO Promotes heat – tolerance (stress tolerance) in C. elegans [7173]. …”
Section: Discussionmentioning
confidence: 99%
“…Because the evolution of multi-drug-resistant pathogens may have developed from the antibiotic resistance genes (transmissible resistance) from probiotic strains, this has become a serious safety issue [73]. Some studies reported that Lactobacillus had high levels of resistance to ampicillin vancomycin and streptomycin [59].…”
Section: Discussionmentioning
confidence: 99%
“…Caenorhabditis elegans is a bacterivorous nematode found in soil and decaying plants where many microbes reside (Burlinson et al, 2013;Choi et al, 2016). It also provides a useful model host for the study of host-bacteria interactions, bacterial pathogenesis and drug development, because it has simple growth requirements, a short generation time and well-established genetic tools (Niu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, C. elegans exhibits chemotaxis to many water-soluble compounds like NaCl, cAMP and small volatile molecules (Bargmann et al, 1993). In C. elegans, fertilized eggs are propelled from the uterus and its egg-laying rate is generally controlled by the availability of food (Dempsey et al, 2005), and it is essential that C. elegans differentiates preferred food sources from pathogenic bacteria (Peng et al, 2016;Choi et al, 2016;Burlinson et al, 2013). On the other hand, several bacteria have evolved a variety of defense mechanisms against bacterivorous nematodes, and thus, it is important that we understand predator-prey interactions via environmental factors, such as signalling molecules and food sources.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, worms are more attracted to and less likely to 552 leave bacterial lawns with this particular smell (63). Indeed, lactic acid bacteria in rotting 553 citrus fruits were more attractive to worms when releasing diacetyl (66). Similarly, 554 entomopathogenic nematodes of the genus Steinernema were more attracted to insect 555 cadavers, when they were infected with the diacetyl-producing bacterial symbionts of the 556 nematode (67).…”
mentioning
confidence: 99%